Is It Dangerous to Live in Neighborhoods with More Immigrants? Assessing the Effects of Immigrant Concentration on Crime Patterns - Han, Sungil; Piquero, Alex R. (Crime and delinquency, 2022)
The immigration-crime nexus has been the subject of much empirical attention and research findings consistently indicate that neighborhoods with large immigrant populations exhibit comparatively lower crime rates. However, it is still imperative to explain how these effects take place in different contexts of structural circumstances of communities. This study aims to examine the effects of immigrant concentration as well as its conditioning effects for racial/ethnic segregation and concentrated disadvantage in Dallas, Texas. Results show that immigrant concentration is negatively associated with crime counts and, most importantly, that immigrant concentration moderates the effect of structural conditions on crime. Generally, immigration has crime-reducing effects and helps ameliorate the negative effects of structural conditions on crime.